Dimensions of the Word - Review Editors (Journal of Dharma, 2000)
Joseph Pathrapankal, Dimensions of the Word, Bangalore: Dharmaram Publications, 2000, pp. xiv+343, Rs. 250.00, US18.00, ISBN: 8186861-262.